PENGARUH PEMBERIAN FINANCIAL INSENTIF DAN KOMUNIKASI INTERNAL TERHADAP SEMANGAT KERJA KARYAWAN PADA PT. TRI BAKTI SARIMAS - Fitri, Fabestia Dede Indah; Ningsih, Dewita Suryati; Pramadewi, Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The aims of this research are to know about the impact of incentive and communication simultanously to the employee’s spirit, to know about the impact of incentive to the employee spirit and to find the impact of communication to the employee’s spirit at PT. Tribakti Sarimas. The population of this study are all the harvesting employee at PT. Tri Bakti Sarimas with amount of 63 people. Considering of the limitation of the population so to determined the sample were using cencus method, so there were 63 people as samples. To analyze the data were using multiple regression. According to the study, simultanously and partially both incentive and communication have a positive and significant effect to the employee’s spirit at PT. Tri Bakti Sarimas. It means that the better of incentive and communication so the employee’s spirit at PT Tri Bakti Sarimas will increase. The independent variable that dominantly impact the employee spirit is incentive.Keywords : Incentive, Communication, Employee Spirit